An Intelligent Greenhouse Control System - Yang Jiaqiang; Jin Yulong; Gao Jian (Institute of Advanced Engineering and Science, 2013)
Because the greenhouse control systems designed in the past are not adaptable in practice, a new greenhouse control system based on RS485 bus is realized in this paper. A new smart sensor block is developed in the system to acquire field environment factor, which can reduce complex routing and increase reliability of the whole system. The model of solar greenhouse is introduced and fuzzy control is adopted in control unit. Besides, a friendly human-computer interface is developed by LabVIEW. The proposed system has been verified by the experiments in the control of medium single-span greenhouses. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3088